Pengaruh Kualitas Pelayanan Kesehatan Terhadap Loyalitas Pasien Rawat Inap di Rumah Sakit Pertamedika Ummi Rosnati Banda Aceh - Sari, Putri Ilham (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
This study aims to examine and see where patient satisfaction lies with the number of patients who have a balance at Pertamedika Ummi Rosnati Hospital Banda Aceh. Patient loyalty is an attitude that describes the patient's commitment to healthcare services by repeatedly utilizing them to meet medical needs. This research aims to determine the influence of healthcare service quality on the loyalty of inpatients at Pertamedika Ummi Rosnati Hospital, Banda Aceh, in 2024. The research method used is quantitative research with Purposive Sampling, involving 30 inpatient respondents. Data collection was conducted through direct interviews with the respondents. The data analysis was performed using the Chi-Square Test. The results show a significant relationship between service quality aspects, including reliability, responsiveness, assurance, and empathy, with a P-value of <0.05, and patient loyalty. However, no significant relationship was found between tangibles and patient loyalty, with a P-value of >0.05, at Pertamedika Ummi Rosnati Hospital, Banda Aceh, in 2024. It is recommended that the hospital further improve the quality of its services to create a positive perception among patients and enhance patient loyalty in using healthcare services at Pertamedika Ummi Rosnati Hospital, Banda Aceh.